Systems theory and Luhmann's musical language - Sugai, Kin Modesto; Santos, Vitorino Modesto dos (Farol, 2024)
This article seeks to analyze, according to Luhmannian theory, two systems, or the framing of musical language in a complex theoretical formulation, applying Luhmann's concepts in the definition of art and in a systemic way of relating to musical language through comparison with theories musicals. . It is suggested that musical language may constitute a structural coupling between the two systems or be specific. The fact that music is something organized and directly related to the musical language does not mean that the creation process is excluded, including the improvised participation of the performer, a condition that guarantees the evolution of the system.